Isolation and Characterization of Copper- and Zinc- Binding Metallothioneins from the Marine Alga Ulva Compressa (Chlorophyta) - Moenne-Munoz, A; Laporte-Poblete, D; Gonzalez-Figueroa, A; Gomez-Luna, M (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
In this work, transcripts encoding three metallothioneins from Ulva compressa (UcMTs) were amplified: The 5′and 3′ UTRs by RACE-PCR, and the open reading frames (ORFs) by PCR. Transcripts encoding UcMT1.1 (Crassostrea-like), UcMT2 (Mytilus-like), and UcMT3 (Dreissena-like) showed a 5′UTR of 61, 71, and 65 nucleotides and a 3′UTR of 418, 235, and 193 nucleotides, respectively. UcMT1.1 ORF encodes a protein of 81 amino acids (MW 8.2 KDa) with 25 cysteines (29.4%), arranged as three motifs CC and nine motifs CXC; UcMT2 ORF encode a protein of 90 amino acids (9.05 kDa) with 27 cysteines (30%), arranged as three motifs CC, nine motifs CXC, and one motif CXXC; UcMT3 encode a protein of 139 amino acids (13.4 kDa) with 34 cysteines (24%), arranged as seven motifs CC and seven motifs CXC. UcMT1 and UcMT2 were more similar among each other, showing 60% similarity in amino acids; UcMT3 showed only 31% similarity with UcMT1 and UcMT2. In addition, UcMTs displayed structural similarity with MTs of marine invertebrates MTs and the terrestrial invertebrate Caenorhabtidis elegans MTs, but not with MTs from red or brown macroalgae. The ORFs fused with GST were expressed in bacteria allowing copper accumulation, mainly in MT1 and MT2, and zinc, in the case of the three MTs. Thus, the three MTs allowed copper and zinc accumulation in vivo. UcMTs may play a role in copper and zinc accumulation in U. compressa. © 2019 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: copper and zinc; expression in bacteria; metal accumulation; metallothioneins; marine alga; Ulva compressa